A matte type tattoo special water transfer paper and a preparation process thereof

CN122980258APending Publication Date: 2026-10-27WEIHAI JUNLIN NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611367446.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

1、本发明通过哑光功能层的创新设计,采用特定粒径的二氧化硅消光粉与丙烯酸类聚合物树脂的优化组合,在图案承载层下方构建精确的光学调控层。转印后的图案呈现60°角光泽度低于10GU的高哑光效果,接近真实纹事的自然质感,消除了常规产品的塑料感和反光缺陷,大幅提升美观度和消费者满意度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122980258A_ABST
    Figure CN122980258A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of special printing material, and relates to a matte type tattoo special water transfer paper and a preparation process thereof. The matte type tattoo special water transfer paper is composed of a base paper layer, a bonding layer, a matte functional layer, a pattern bearing layer and a protective layer in sequence. The bonding layer comprises modified starch, modified cellulose paste, natural rubber emulsion, polyol functional additive and hydrophilic wetting additive. The matte functional layer comprises a PET film or PVC film substrate, is supplemented with an acrylic polymer resin, is added with silica matt powder, and further comprises an anionic high molecular dispersant and a water-based polyurethane stabilizer. The pattern bearing layer comprises a water-based acrylic resin, an edible film-forming emulsion, a color paste wetting additive, a weather-resistant color retention additive and a natural compound. The protective layer comprises a PET film or PVC film and a citrate plasticizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of special printing materials technology, and more specifically, to a matte water transfer paper for tattoos and its preparation process. Background Technology

[0002] Tattooing, as a form of body art, has gained increasing popularity among consumers worldwide in recent years. Compared to traditional permanent tattoos, temporary tattoos offer advantages such as being painless, non-invasive, allowing for changeable designs, and being safe and convenient, leading to a continuous increase in market demand. Water transfer printing technology is the core technology for transferring temporary tattoo designs. Its principle involves wetting transfer paper with a printed design, causing the design layer to separate from the substrate and transfer to the surface of the skin.

[0003] Existing water transfer printing paper for tattoos has the following technical problems in practical applications: First, there's the issue of gloss. The pattern-carrying layer of conventional water transfer printing paper typically has a high-gloss or semi-gloss finish. When transferred to the skin, this results in a noticeable plastic-like or reflective effect, significantly different from the matte texture of a real tattoo, affecting aesthetics and realism. Consumer demand for temporary tattoo products with a natural matte finish is increasingly strong.

[0004] Second, there is the issue of interlayer bonding strength. The multi-layered structure of water transfer printing paper requires controllable separation under wet conditions, meaning the pattern carrier layer must peel off easily from the protective layer while adhering firmly to the skin. Existing products often struggle to balance the conflicting requirements of "easy peeling" and "high adhesion," resulting in a high transfer failure rate or incomplete pattern transfer.

[0005] Third, there are biosafety concerns. Tattoo water transfer paper comes into direct contact with human skin, and some products use industrial-grade raw materials or contain potentially irritating ingredients (such as heavy metal pigments, non-food-grade film-forming substances, etc.), which may cause skin allergies or other health risks. As international regulations tighten safety standards for cosmetics and personal care products, developing entirely food-grade or naturally derived pattern carrier systems has become an industry trend.

[0006] Fourth, insufficient weather resistance and color retention. Temporary tattoos are exposed to sunlight, sweat, and friction during use. The color fastness and pattern durability of existing products are generally poor, usually only lasting 1-3 days, and are prone to fading and smudging.

[0007] Fifth, the transfer printing experience is unsatisfactory. The wetting speed and uniformity of existing products are not ideal, requiring consumers to wait a long time or press repeatedly to achieve a complete transfer, thus the ease of use needs to be improved. Summary of the Invention

[0008] This invention provides a matte water transfer paper for tattoos, which solves the problems of unnatural gloss, poor interlayer bonding, insufficient biocompatibility and poor weather resistance in existing technologies through an innovative multi-layer composite structure design.

[0009] Another objective of this invention is to provide a preparation process for the above-mentioned matte tattoo-specific water transfer paper, so as to achieve precise construction and efficient composite of each functional layer.

[0010] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a matte water transfer paper for tattoos, which is composed of a base paper layer, an adhesive layer, a matte functional layer, a pattern carrier layer and a protective layer in sequence; The adhesive layer is prepared from modified starch, modified cellulose slurry, natural rubber latex, polyol functional additives, and hydrophilic wetting agents; The matte functional layer is made of PET film or PVC film substrate, acrylic polymer resin, silica matting powder, anionic polymer dispersant and waterborne polyurethane stabilizer. The pattern carrier layer is made of water-based acrylic resin, food-grade film-forming emulsion, color paste wetting agent, weather-resistant color retention agent and natural compounds; The protective layer includes PET film or PVC film and citrate ester plasticizer.

[0011] Preferably, the mass fractions of each component in the adhesive layer are: 20-40 parts modified starch, 10-25 parts modified cellulose, 15-30 parts natural rubber latex, 5-15 parts polyol functional additives, and 2-8 parts hydrophilic wetting additives.

[0012] Preferably, the modified starch is obtained by adding a slip agent to a starch gelatinization solution; The modified cellulose is pretreated with carboxymethylation, then swells uniformly in water, and is subsequently homogenized under high pressure to dissociate the fibers into nanocellulose.

[0013] Preferably, the method for preparing the modified starch includes: The original starch is prepared into a starch milk with a mass fraction of 5%~15%, heated to 60~95℃ for gelatinization, and after gelatinization, 0.5%-3% of the dry starch mass of the lubricant organic fluorine modified polysiloxane or oxidized polyethylene is added. After stirring evenly, it is dried, pulverized and sieved to obtain modified starch. The fluorine-modified polysiloxane has a fluorine content of 5% to 20% and a molecular weight of 3000 to 15000; the oxidized polyethylene has a molecular weight of 1000 to 5000 and an acid value of 15 to 30 mg KOH / g.

[0014] Preferably, the method for preparing the modified cellulose pulp includes: Cellulose raw materials are pretreated by carboxymethylation in a mixed solution of sodium hydroxide and monochloroacetic acid with a degree of substitution of 0.3 to 0.8. The resulting sodium carboxymethyl cellulose is placed in deionized water to prepare a suspension with a mass fraction of 1% to 5%. After full swelling, it is circulated 5 to 20 times under a pressure of 50 to 150 MPa by a high-pressure homogenizer to dissociate and obtain nanocellulose with a diameter of 10 to 20 nm and a length of 200 to 1000 nm. The cellulose raw material is selected from at least one of bleached softwood pulp, bleached hardwood pulp, cotton pulp, or bamboo pulp; the homogenizing valve gap of the high-pressure homogenizer is 50~200μm, and the temperature is 20~60℃.

[0015] Preferably, the polyol functional additive is selected from at least one of propylene glycol, glycerol, sorbitol, or polyethylene glycol; The hydrophilic wetting agent is selected from at least one of alkyl glycosides, fatty alcohol polyoxyethylene ethers, or succinate sulfonates.

[0016] Preferably, the acrylic polymer resin is an aqueous acrylic emulsion or an acrylic-polyurethane copolymer emulsion, with a solid content of 30%-50%. The silica matting agent is fumed silica or precipitated silica with an average particle size of 1-5 μm, and the amount added is 5%-20% of the solid content of the acrylic polymer resin. The anionic polymeric dispersant is sodium polyacrylate or sodium polystyrene-maleic anhydride copolymer; the waterborne polyurethane stabilizer is ionic waterborne polyurethane or self-emulsifying waterborne polyurethane.

[0017] Preferably, the mass fractions of each component in the pattern carrier layer are: 20-35 parts of waterborne acrylic resin, 10-20 parts of food-grade film-forming emulsion, 1-5 parts of color paste wetting agent, 30-50 parts of deionized water, 2-6 parts of weather-resistant color-preserving agent, and 0.5-3 parts of natural compound. The natural compound is genipin or genipin acid; The food-grade film-forming emulsion is selected from at least one of gum arabic, gelatin, or chitosan emulsion; the color paste wetting aid is selected from polyether-modified polysiloxane or fluorocarbon surfactant. The weather-resistant and color-preserving additive is a compound of ultraviolet absorber and antioxidant. The ultraviolet absorber is selected from at least one of UV-9, titanium dioxide or zinc oxide, and the antioxidant is selected from at least one of tocopheryl acetate or food-grade BHT.

[0018] Preferably, the citrate plasticizer is selected from at least one of acetylated tributyl citrate, triethyl citrate, acetylated triethyl citrate, or trioctyl citrate, and the amount added is 20% to 40% of the mass of the PVC substrate or 5% to 15% of the mass of the PET substrate.

[0019] Preferably, the thicknesses of each layer are as follows: base paper layer 80~150μm, adhesive layer 5~20μm, matte functional layer 10~30μm, pattern carrier layer 15~40μm, and protective layer 12~50μm.

[0020] Secondly, the present invention provides a preparation process for matte tattoo-specific water transfer paper, comprising the following steps: (1) Pretreatment of the base paper layer: The base paper layer is subjected to corona treatment or coated with a base adhesive to enhance surface adhesion; (2) Adhesive layer coating: Modified starch, modified cellulose, natural rubber latex, polyol functional additives and hydrophilic wetting additives are mixed evenly and coated on the surface of the pretreated base paper layer, and then dried to form an adhesive layer; (3) Preparation of matte functional layer: Using PET film or PVC film as substrate, a matte functional coating is applied to one side of the substrate. The coating includes acrylic polymer resin, silica matting powder, anionic polymer dispersant, waterborne polyurethane stabilizer and deionized water, and is dried to form a matte functional layer. (4) Composite: The matte functional layer obtained in step (3) is hot-pressed with the smooth surface of the film substrate facing the adhesive layer and the matte coating surface obtained in step (2) facing upwards to obtain a composite semi-finished product; (5) Pattern carrier layer coating: The pattern carrier layer coating is applied to the matte coating surface of the composite semi-finished product obtained in step (4). The coating includes water-based acrylic resin, food-grade film-forming emulsion, color paste wetting agent, deionized water, weather-resistant color retention agent and natural compound, and is dried to form a pattern carrier layer. (6) Protective layer lamination: Using PET film or PVC film as the protective layer substrate, apply citrate ester plasticizer to its surface, with the side coated with plasticizer facing the direction of the pattern carrier layer, and lightly press and laminate it with the semi-finished product obtained in step (5). (7) Curing and slitting: The semi-finished product obtained in step (6) is cured in an environment with a temperature of 20~30℃ and a relative humidity of 45%~60% for 12~24 hours, and then slitting and rolling to obtain matte tattoo water transfer paper.

[0021] Preferably, in step (4), the hot-pressing composite temperature is 80~120℃ and the pressure is 0.3~0.8MPa; in step (6), the hot-pressing composite temperature is 100~150℃ and the pressure is 0.5~1.0MPa.

[0022] Preferably, in step (5), the gradient heating drying is performed by first pre-drying at 40~50℃ for 5~10 min, then by main drying at 60~70℃ for 10~20 min, and finally by final drying at 80~90℃ for 5~10 min.

[0023] In summary, the present invention has the following beneficial effects: 1. This invention utilizes an innovative matte functional layer design, employing an optimized combination of silica matte powder with a specific particle size and acrylic polymer resin to construct a precise optical control layer beneath the pattern carrier layer. The transferred pattern exhibits a high matte effect with a gloss level of less than 10 GU at a 60° angle, closely resembling the natural texture of real-life patterns. This eliminates the plastic feel and reflective defects of conventional products, significantly improving aesthetics and consumer satisfaction.

[0024] 2. In this invention, the adhesive layer adopts a ternary composite system of modified starch, nanocellulose, and natural rubber latex, combined with the synergistic effect of polyol and hydrophilic wetting agent, achieving high bonding strength in the dry state and controllable weakening and separation under wet conditions. During product storage, the layers remain firmly bonded without delamination. During transfer printing, moisture penetrates quickly, the pattern layer peels off smoothly, and the transfer success rate is significantly improved.

[0025] 3. The pattern carrier layer in this invention uses food-grade or cosmetic-grade raw materials throughout: edible film-forming emulsions (gum arabic, gelatin, chitosan), natural compound genipin, food-grade water-based acrylic resin, etc., eliminating the use of harmful industrial-grade substances at the source. The product complies with relevant standards such as EU EC 1223 / 2009 cosmetic regulations and US FDA 21 CFR, and is suitable for a wide range of consumers, including those with sensitive skin.

[0026] 4. This invention significantly improves the lightfastness, sweat resistance, and abrasion resistance of the transferred pattern through the synergistic combination of ultraviolet absorbers and antioxidants in the weather-resistant and color-preserving additives (and the water-retaining and adhesive effects of natural film-forming substances). Under normal use conditions, the color development and durability can reach 5-7 days, which is more than twice as long as conventional products.

[0027] 5. The introduction of hydrophilic wetting agents in this invention significantly accelerates the penetration and spreading of moisture at the interlayer interface, shortening the wetting waiting time; the slippery properties of modified starch reduce peeling resistance; and gradient heating drying ensures the uniformity and smoothness of the pattern-bearing layer. These comprehensive optimizations make the transfer operation more convenient and efficient, enhancing the consumer experience.

[0028] 6. The main raw materials in this invention are derived from natural renewable resources (starch, cellulose, rubber, gum arabic, etc.), and the preparation process uses water as the main solvent, resulting in low VOC emissions, which is in line with the trend of green manufacturing and sustainable development.

[0029] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit the scope of protection of the present invention. Attached Figure Description

[0030] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 Comparison image of the matte tattoo-specific water transfer paper prepared for this application and ordinary water transfer paper. Detailed Implementation

[0031] The present invention will be further described in detail below with reference to the embodiments. It should be noted that: unless otherwise specified, the conditions in the following embodiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following embodiments can be obtained from commercially available sources.

[0032] The matte tattoo-specific water transfer paper of this invention adopts a five-layer composite structure, consisting of a base paper layer, an adhesive layer, a matte functional layer, a pattern-carrying layer, and a protective layer, which are sequentially laminated together. Each layer has a clearly defined function, and their synergistic effect achieves the comprehensive performance of the final product.

[0033] 1. Base paper layer The base paper layer, serving as the supporting substrate for the entire composite structure, requires certain mechanical strength, dimensional stability, and water absorption and wettability. This invention selects wood pulp paper or synthetic fiber paper with a basis weight of 80-150 g / m², and a thickness controlled within the range of 80-150 μm. The base paper layer needs to undergo pretreatment to enhance surface adhesion and provide an active interface for the subsequent coating of the adhesive layer.

[0034] 2. Adhesive layer The adhesive layer is one of the key functional layers of this invention. It is set between the base paper layer and the matte functional layer. Its core functions are: (1) to achieve a firm bond between the base paper layer and the matte functional layer, ensuring the structural integrity of the product in a dry state; (2) under wet conditions, through the water-sensitive design of the components, to moderately reduce the interlayer bonding strength, creating conditions for controllable separation during subsequent transfer printing; (3) to provide appropriate flexibility and smoothness, improving the processing performance and transfer feel of the product.

[0035] The aforementioned adhesive layer comprises the following components: modified starch, modified cellulose, natural rubber latex, polyol functional additives, and hydrophilic wetting agents.

[0036] Modified starch, used as the main film-forming material in the adhesive layer, is derived from the green modification of natural starch. This invention employs a specific slip agent to modify the starch after gelatinization. The slip agent is selected from organofluorine-modified polysiloxanes or oxidized polyethylene. The organofluorine-modified polysiloxanes have a fluorine content of 5%-20% and a molecular weight of 3000-15000; the oxidized polyethylene has a molecular weight of 1000-5000 and an acid value of 15-30 mgKOH / g. The introduction of the slip agent imparts excellent slipperiness and the ability to reduce the surface friction coefficient to the modified starch film, which is crucial for the smooth peeling of the pattern layer during the transfer process. The amount of modified starch used is 20-40 parts by weight.

[0037] Modified cellulose slurry is used as a reinforcing component, employing nanoscale cellulose materials. This invention prepares nanocellulose with a diameter of 10-20 nm and a length of 200-1000 nm by pretreating cellulose raw materials with carboxymethylation followed by high-pressure homogenization dissociation technology. The high aspect ratio and abundant surface hydroxyl and carboxyl groups of the nanocellulose enable it to form a three-dimensional network reinforcement structure in the adhesive layer, significantly improving interlayer bonding strength and the tear resistance of the membrane. Simultaneously, the hydrophilicity of the carboxymethyl groups allows the nanocellulose to hydrate rapidly upon wetting, promoting water penetration and controllable weakening of the interlayer interface. The amount of modified cellulose used is 10-25 parts by weight.

[0038] Natural rubber latex, as an elastomer component, imparts excellent flexibility and resilience to the adhesive layer. The cis-1,4-polyisoprene molecular chain structure of natural rubber enables the film layer to maintain high elasticity over a wide temperature range, effectively buffering stress concentration in the composite structure during use and preventing interlayer cracking or delamination. The amount of natural rubber latex used is 15-30 parts by weight.

[0039] Polyol functional additives, acting as plasticizers and humectants, are selected from at least one of propylene glycol, glycerol, sorbitol, or polyethylene glycol. The multiple hydroxyl groups in polyol molecules can form hydrogen bonds with the molecular chains of starch and cellulose, disrupting the original crystalline regions and increasing the mobility of the molecular chain segments, thereby improving the flexibility and anti-brittleness of the film layer. Simultaneously, the hygroscopic and moisturizing properties of polyols help regulate the water-sensitive response speed of the adhesive layer, ensuring stable product performance under varying environmental humidity. The dosage of polyol functional additives is 5-15 parts by weight.

[0040] Hydrophilic wetting agents, as surfactants, are selected from at least one of alkyl glycosides (APG), fatty alcohol polyoxyethylene ethers (AEO), or succinate sulfonates. These agents significantly reduce the surface tension of the adhesive coating solution and the dried film layer, improving the wetting and spreading properties of the base paper layer and the matte functional layer, ensuring uniform and defect-free coating. In transfer printing, hydrophilic wetting agents accelerate the penetration and spreading of moisture at the interlayer interface, shorten wetting time, and enhance the user experience. The dosage of the hydrophilic wetting agent is 2-8 parts by weight.

[0041] The synergistic mechanism of the components in the adhesive layer is as follows: modified starch and modified cellulose form an interpenetrating network structure, natural rubber latex is dispersed in the network in the form of microparticles to form an "island structure", polyols fill the gaps in the network to play a plasticizing and moisturizing role, and hydrophilic wetting agents are distributed at the interface to reduce surface tension. In the dry state, hydrogen bonding, entanglement, and physical anchoring of rubber microparticles make the interlayer bonding strong; when wetted, water molecules penetrate rapidly, and the hydration and swelling of starch and cellulose, the surface activation of rubber microparticles, and the solubilizing effect of additives together lead to a controllable decrease in interfacial bonding strength, achieving the responsive characteristics of "dry adhesion and wet delamination".

[0042] The separation interface of the present invention is located between the adhesive layer and the matte functional layer; in the dry state, the adhesive layer and the matte layer are bonded together with moderate strength; after being wetted with water, the starch and cellulose in the adhesive layer quickly hydrate and swell, the interfacial bonding force decreases rapidly, and the pattern layer and the matte layer are smoothly separated from the base paper.

[0043] 3. Matte functional layer The matte functional layer is the key layer for achieving the core visual effect and matte texture of this invention, and it is located between the adhesive layer and the pattern carrier layer. This layer simultaneously serves the dual functions of optical control and structural transition.

[0044] The matte functional layer includes a PET film or PVC film substrate, supplemented with an acrylic polymer resin, with added silica matting powder, and also includes an anionic polymeric dispersant and a waterborne polyurethane stabilizer.

[0045] PET or PVC film substrates serve as the structural carrier for the matte functional layers, providing basic mechanical strength and thermal lamination processability. PET film exhibits excellent dimensional stability, temperature resistance, and barrier properties; PVC film offers better flexibility and cost advantages. The substrate thickness is determined based on the overall thickness design requirements, typically ranging from 10-30 μm.

[0046] Acrylic polymer resins, used as binders and film-forming substances for matte powders, are selected from water-based acrylic emulsions or acrylic-polyurethane copolymer emulsions, with a solid content of 30%-50%. Acrylic resins possess excellent transparency, weather resistance, and compatibility with adjacent layers. Their refractive index after film formation is close to that of silica matte powder (refractive index approximately 1.46), which helps reduce interfacial losses from light scattering, resulting in a natural matte effect rather than a "whitening" opaque feel.

[0047] Silica matting powder, selected from fumed silica or precipitated silica, serves as the core matting filler. Its average particle size is 2-10 μm, and its addition amount is 5%-20% of the solid content of the acrylic polymer resin. The silica particles form a microscopic rough structure on the surface of the resin film, causing diffuse reflection of incident light rather than specular reflection, thereby reducing gloss. The particle size selection must balance matting efficiency and film transparency: too small a particle size results in insufficient matting, while too large a particle size leads to film turbidity and decreased mechanical properties. The particle size range of this invention has been optimized, and combined with a specific acrylic resin system, it can achieve a high matte effect with a gloss level below 10 GU at a 60° angle, while maintaining clear color rendering of the patterned layer.

[0048] Anionic polymeric dispersants, selected from sodium polyacrylate or sodium polystyrene-maleic anhydride copolymer, are used to ensure the stable dispersion of silica matting agents in resin systems. These dispersants prevent the agglomeration and sedimentation of matting agent particles through electrostatic repulsion and steric hindrance, ensuring the storage stability of the coating solution and the optical uniformity of the coating film.

[0049] Waterborne polyurethane stabilizers, selected from ionic or self-emulsifying waterborne polyurethanes, are used to improve the overall stability and composite adaptability of matte functional layers. The introduction of polyurethane enhances the flexibility and abrasion resistance of the film, while the polar groups on its molecular chains help improve the interfacial bonding strength with adjacent adhesive layers and pattern carrier layers.

[0050] The matte functional layer lamination process employs a "coating-drying-hot pressing" method: first, a matte coating is applied to one side of the film substrate, dried to form a matte surface, and then laminated with the base paper layer / adhesive layer through hot pressing. This process ensures that the matte structure is precisely constructed beneath the pattern carrier layer, resulting in a natural matte effect from the inside out for the final transferred pattern.

[0051] 4. Pattern carrier layer The pattern carrier layer is the functional layer that directly carries the tattoo pattern and transfers it to the skin. Its performance directly determines the color rendering effect, biocompatibility, and durability of the final product.

[0052] The pattern carrier layer comprises water-based acrylic resin, food-grade film-forming emulsion, color paste wetting agent, weather-resistant color retention agent, and natural compounds.

[0053] Waterborne acrylic resin is used as the main film-forming substance for the pattern carrier layer, with a dosage of 20-35 parts by weight. Food-grade or cosmetic-grade waterborne acrylic emulsions are selected, possessing good film-forming properties, transparency, and skin adhesion. The glass transition temperature (Tg) of the acrylic resin has been optimized to ensure that the film layer maintains appropriate softness and tack at room temperature, facilitating the transfer process and forming a flexible and abrasion-resistant protective film after transfer.

[0054] Food-grade film-forming emulsions, used as auxiliary film-forming substances, are applied in amounts of 10-20 parts by weight and are selected from at least one of gum arabic, gelatin, or chitosan emulsions. These natural polymeric film-forming substances possess excellent water solubility and biocompatibility, enabling them to regulate the water-responsive characteristics of the film layer—rapidly hydrating and releasing the pattern during transfer, and forming a water-retaining film layer with good skin affinity after transfer. The low viscosity of gum arabic improves coating processability; the gelling properties of gelatin impart temperature-sensitive reversibility to the film layer; and the cationic properties of chitosan facilitate electrostatic adsorption with the stratum corneum of the skin, enhancing pattern durability.

[0055] Pigment wetting aids are used to ensure uniform dispersion of pigments or dyes in the system and leveling properties during coating. They are used in amounts of 1-5 parts by weight and are selected from polyether-modified polysiloxanes or fluorocarbon surfactants. These aids have extremely low surface tension, effectively wetting the surface of organic or inorganic pigment particles, preventing flocculation and floating, and ensuring color saturation and clarity during printing.

[0056] Weather-resistant color-retaining additives are used to improve the lightfastness, oxidation resistance, and perspiration resistance of designs, and are used in amounts of 2-6 parts by weight. These additives are a compound of ultraviolet absorbers and antioxidants. The ultraviolet absorber is selected from at least one of UV-9, titanium dioxide, or zinc oxide, and can effectively absorb ultraviolet light in the 280-400nm wavelength band, preventing photodegradation and fading of the pigment. The antioxidant is selected from at least one of tocopheryl acetate or food-grade BHT, and inhibits oxidation chain reactions by capturing free radicals or decomposing hydrogen peroxide. The synergistic combination of these two additives extends the colorfastness of temporary tattoos from the usual 1-3 days to 5-7 days.

[0057] Natural compounds, selected from genipin or genipin acid, are used as special functional additives at a dosage of 0.5-3 parts by weight. Genipin is a natural iridoid compound extracted from gardenia fruit, possessing unique skin-developing properties. It reacts with amino acids on the skin surface to generate a blue-black natural pigment, mimicking the color development mechanism of real tattoos. This invention adds genipin as an auxiliary color developer to the pattern carrier layer, causing a slight "secondary color development" reaction after the transferred pattern comes into contact with the skin, enhancing the integration and three-dimensionality of the pattern with the skin. Simultaneously, the natural source of genipin ensures biocompatibility.

[0058] The pattern carrier layer is coated using a gradient temperature drying process to precisely control the drying rate and internal structure of the film. Rapid high-temperature drying can easily lead to surface skinning, internal solvent retention, and stress cracking of the film. The gradient temperature process of this invention achieves stable solvent evaporation and uniform curing of the film through graded temperature control in three stages: pre-drying, main drying, and final drying.

[0059] 5. Protective layer The protective layer is located on the outside of the pattern carrier layer (i.e., the side away from the base paper layer). It protects the pattern carrier layer from mechanical damage, contamination and premature aging during storage and transportation. When used for transfer printing, it needs to be easily peeled off from the pattern carrier layer.

[0060] The aforementioned protective layer includes PET or PVC film and citrate-based plasticizers.

[0061] PET film or PVC film serves as the structural substrate of the protective layer, providing mechanical protection and barrier functions. PVC film is the preferred option for the protective layer of this invention due to its good compatibility with plasticizers.

[0062] Citrate ester plasticizers represent a significant improvement over traditional technologies in this invention. Existing technologies commonly use phthalate plasticizers (such as DOP, DBP, DINP, etc.), but these substances are listed as Substances of Very High Concern (SVHC) by the EU REACH regulation and the US FDA, exhibiting potential endocrine disruption and reproductive toxicity, making them unsuitable for tattoo products that come into direct contact with the skin. This invention innovatively uses citrate ester plasticizers to replace phthalates. The citrate ester plasticizer is selected from at least one of triethyl citrate (TEC), tributyl citrate (TBC), acetylated tributyl citrate (ATBC), or trioctyl citrate (TOC). Citrate ester plasticizers are derived from the fermentation of citric acid, possess excellent biodegradability, non-toxicity, and skin compatibility, and have been approved by the FDA for use in food packaging and pharmaceutical fields. In the protective layer, the functions of citrate plasticizers include: (1) adjusting the flexibility of the protective film to facilitate the roll-up and packaging of the product; (2) forming a weak adhesion layer at the contact interface with the pattern carrier layer to achieve convenient peeling with "light peel"; (3) their good volatility ensures that there is no residual odor after the transfer.

[0063] Coating methods for citrate ester plasticizers: For PET film substrates, the plasticizer is directly coated onto one side of the film surface, with the coating amount determined based on the substrate quality and adhesion requirements; for PVC substrates, the plasticizer can be blended with PVC resin and extruded into a film, or applied to the PVC film surface by coating. The plasticizer coating surface faces the pattern carrier layer, and a peelable protective structure is formed by light pressure lamination.

[0064] This invention also provides a preparation process for the above-mentioned matte tattoo-specific water transfer paper, comprising the following steps: Step (1): Pretreatment of the base paper layer The base paper layer is subjected to corona treatment or a primer coating to enhance surface energy and improve polarity, thereby increasing the adhesion of subsequent adhesive layers. The corona treatment power is optimized according to the base paper material and operating speed; the primer can be a water-based polyurethane or a modified acrylic primer, with a coating amount of 1-3 g / m², which forms an extremely thin activation layer after drying.

[0065] Step (2): Applying the adhesive layer Modified starch, modified cellulose, natural rubber latex, polyol functional additives, and hydrophilic wetting agents are mixed evenly according to the formula ratio. A step-by-step mixing method is recommended: first, disperse the modified starch and modified cellulose in a portion of deionized water and stir at high speed to form a homogeneous slurry; add the polyol functional additives and continue stirring; slowly add the natural rubber latex, controlling the stirring speed to prevent emulsion breaking; finally, add the hydrophilic wetting agent and stir at low speed to defoam. The prepared adhesive coating solution is then applied to the surface of the pretreated base paper layer. Coating methods include blade coating, roller coating, or slot extrusion coating. The wet coating amount is calculated and controlled based on the solid content and dry film thickness requirements. After coating, the paper is dried in an oven at 80-120℃ for 1-3 minutes to form an adhesive layer with a thickness of 5-20 μm.

[0066] Step (3): Matte functional layer lamination A matte functional coating is applied to one side of a PET or PVC film substrate. The coating comprises an acrylic polymer resin, silica matting agent, an anionic polymeric dispersant, a waterborne polyurethane stabilizer, and deionized water.

[0067] During preparation, the silica matting powder is first pre-dispersed in anionic polymeric dispersant and a portion of acrylic polymer resin. This pre-dispersed powder is then milled or high-speed dispersed until a fineness ≤15μm is achieved. It is then mixed evenly with the remaining resin and water-based polyurethane stabilizer, and deionized water is added to adjust the viscosity to a suitable coating viscosity. The coating solution is then evenly applied to one side of a PET or PVC film substrate. Coating methods include blade coating, roller coating, or curtain coating. The coating amount is determined based on the required dry film thickness. Drying at 60-100℃ forms a matte functional layer. The drying time is adjusted according to the coating amount and oven conditions to ensure complete drying and that the matting powder particles form a stable micro-rough structure on the resin surface.

[0068] Step (4): Composite The matte functional layer obtained in step (3) is hot-pressed with the smooth surface of the film substrate facing the adhesive layer and the matte coating surface obtained in step (2) facing upwards to obtain a composite semi-finished product.

[0069] This orientation is a key process control point in this invention. The smooth surface of the film substrate contacts the adhesive layer, achieving a strong bond through hot pressing; the matte coating surface faces upwards, providing a matte base for the subsequent pattern carrier layer coating. The hot pressing temperature is 80-120℃, and the pressure is 0.3-0.8MPa. Hot pressing softens and flows the thermoplastic components in the adhesive layer, forming molecular entanglements and localized mutual dissolution with the smooth surface of the film substrate of the matte functional layer, achieving a strong bond. The pressure must be moderate: too low a pressure will result in weak bonding and easy bubble formation, while too high a pressure may cause the micro-rough structure of the matte coating to deform under pressure and reduce the matte effect.

[0070] Step (5): Coating of the pattern carrier layer A pattern carrier layer coating is applied to the matte coating surface of the composite semi-finished product obtained in step (4). The coating includes water-based acrylic resin, food-grade film-forming emulsion, color paste wetting agent, deionized water, weather-resistant color-preserving agent, and natural compounds.

[0071] Mix all components thoroughly according to the formula ratio. The colorant can be added at this stage, or a portion of the resin can be reserved as an ink carrier and added later during printing. Apply the thoroughly mixed coating solution to the matte coating surface. The coating method depends on the pattern formation process: if a blank layer is pre-coated before printing the pattern, a uniform full-coat method is used; if the pattern-containing colorant is directly coated, gravure printing or flexographic printing can be used. After coating, dry to form the pattern carrier layer. The drying process can use gradient temperature drying: first, pre-dry at 40-50℃ for 5-10 minutes to allow initial film formation on the film surface and prevent sagging; then, main dry at 60-70℃ for 10-20 minutes to allow the main solvent to evaporate and the film layer to gradually solidify; finally, final dry at 80-90℃ for 5-10 minutes to ensure that residual solvent is fully removed and the film layer reaches a stable state. Gradient temperature drying forms a pattern carrier layer with a thickness of 15-40μm.

[0072] Step (6): Protective layer lamination Using PET film or PVC film as the protective layer substrate, a citrate ester plasticizer is coated on its surface, with the side coated with plasticizer facing the direction of the pattern carrier layer, and lightly pressed and laminated with the semi-finished product obtained in step (5).

[0073] Citrate ester plasticizers can be applied by roller coating, blade coating, or spray coating. The coating amount is optimized according to the type of substrate and peel strength requirements of the protective layer: for PET film, the coating amount is usually 5-15 g / m²; for PVC film, the coating amount can be appropriately increased to 15-30 g / m². Light pressure lamination is a key feature of this step—unlike the strong hot-press lamination in step (4), the protective layer lamination adopts a "light pressure" method, with the pressure controlled at 0.1-0.3 MPa and the temperature controlled at 40-60℃. The purpose of light pressure is only to make the plasticizer coating surface and the pattern carrier layer form a uniform adhesion, without forming a strong chemical bond or deep molecular diffusion. This weak bond ensures that consumers can easily remove the protective layer when using it for transfer printing, without leaving residues on the surface of the pattern carrier layer or causing damage to the pattern.

[0074] Step (7): Cooking and Slicing The semi-finished product obtained in step (6) is aged in an environment with a temperature of 20-30℃ and a relative humidity of 45%-60% for 12-24 hours, and then cut and rolled to obtain matte tattoo-specific water transfer paper.

[0075] The selection of curing conditions is based on the following considerations: a temperature of 20-30℃, close to room temperature, to avoid excessive migration of plasticizers or abnormal strengthening of interlayer bonding caused by high temperatures; a relative humidity of 45%-60% to ensure the product's moisture content reaches a balanced state, preventing embrittlement due to excessive dryness or adhesion due to excessive moisture. A curing time of 12-24 hours allows for sufficient stress relaxation at each layer interface, stabilizing the interlayer bonding strength, while further evaporation of residual trace solvents, resulting in a balanced product performance. After curing, the product is slit, wound, and packaged to obtain the matte tattoo-specific water transfer paper.

[0076] Example Example 1 The preparation process of matte tattoo-grade water transfer paper includes the following steps: (1) Preparation of modified starch Cassava starch was prepared into a starch slurry with a mass fraction of 10%, and then heated to 85°C for 30 minutes with stirring to gelatinize. After gelatinization, 1.5% (by dry starch mass) of an organofluorine modified polysiloxane lubricant (fluorine content 12%, molecular weight 8000) was added, and stirring was continued for 20 minutes until homogeneous. The modified starch slurry was then dried by drum drying, pulverized, and passed through a 100-mesh sieve to obtain modified starch.

[0077] (2) Preparation of modified cellulose pulp Bleached softwood pulp was pretreated with carboxymethylation by immersing it in a mixed solution of sodium hydroxide and monochloroacetic acid (molar ratio NaOH:ClCH2COOH = 2.5:1) to control the degree of substitution at 0.55. After the reaction, the pulp was washed and dehydrated to obtain sodium carboxymethyl cellulose. A 3% (w / w) suspension was prepared in deionized water and allowed to swell for 12 hours. The suspension was then circulated 10 times using a high-pressure homogenizer at 100 MPa pressure, with a homogenization valve gap of 100 μm and a temperature of 40 °C. Dissociation yielded cellulose nanoparticles with a diameter of 15 nm and a length of 600 nm.

[0078] (3) Preparation of adhesive coating liquid Weigh the following components by weight: 30 parts modified starch, 18 parts modified cellulose, 22 parts natural rubber latex (60% solids content), 10 parts glycerol, 5 parts alkyl glycoside (APG0810), and 80 parts deionized water. Mix thoroughly in stages: First, disperse the modified starch and modified cellulose in deionized water and stir at high speed for 30 minutes; add glycerol and continue stirring for 15 minutes; slowly add the natural rubber latex and reduce the stirring speed to 500 rpm and stir for 20 minutes; finally, add the alkyl glycoside and stir at low speed for 10 minutes. Adjust the viscosity to 25-35 seconds using a Forecast cup 4.

[0079] The prepared adhesive coating solution was applied to the surface of the corona-pretreated base paper (120 g / m² wood pulp base paper, single-sided corona treatment, power density 8 W·min / m²) using a doctor blade coating method. The wet coating amount was 80 g / m², and the paper was dried at 110℃ for 2 min to form an adhesive layer with a thickness of 12 μm.

[0080] (4) Preparation of matte functional layer Weigh out 100 parts of waterborne acrylic emulsion (40% solid content), 8 parts of precipitated silica matting agent (average particle size 5μm), 2 parts of sodium polyacrylate dispersant, 5 parts of ionic waterborne polyurethane stabilizer, and 30 parts of deionized water. First, premix the matting agent and dispersant with 30 parts of emulsion, disperse them in a high-speed disperser for 30 minutes, and then mill them to a fineness ≤10μm. Finally, mix them evenly with the remaining emulsion, stabilizer, and deionized water.

[0081] Using PET film (12μm thick) as the substrate, a matte functional coating is applied to one side of the substrate by roller coating at a wet coating amount of 60g / m² and dried at 80℃ for 3min to form a matte functional layer.

[0082] (5) Composite The matte functional layer obtained in step (4) is hot-pressed with the smooth side of the PET film facing the adhesive layer obtained in step (3) and the matte coating side facing upwards. The hot-pressing temperature is 100℃, the pressure is 0.5MPa, and the lamination speed is 15m / min to obtain the composite semi-finished product.

[0083] (6) Pattern carrier layer coating Weigh the following components by weight: 28 parts water-based acrylic resin (Tg=15℃, solid content 45%), 15 parts gum arabic latex (solid content 30%), 3 parts polyether-modified polysiloxane wetting agent, 40 parts deionized water, 1.5 parts UV-9, 1 part tocopheryl acetate, and 1 part genipin. After mixing thoroughly, add 20 parts of pre-dispersed cosmetic-grade black pigment (pigment content 15%) and stir at low speed until homogeneous.

[0084] The pattern carrier layer coating is applied to the matte coating surface of the composite semi-finished product obtained in step (5) by gravure printing, and then dried by gradient heating: pre-drying at 45℃ for 8 min, main drying at 65℃ for 15 min, and final drying at 85℃ for 8 min to form a pattern carrier layer with a thickness of 25 μm.

[0085] (7) Protective layer composite Using a PET film (20 μm thick) as the protective layer substrate, acetylated tributyl citrate (ATBC) plasticizer is coated on one side of the film using a roller coating method, with a coating amount of 10 g / m². With the side coated with ATBC facing the pattern carrier layer, the film is lightly pressed and laminated with the semi-finished product obtained in step (6) at a temperature of 50°C and a pressure of 0.2 MPa.

[0086] (8) Cooking and cutting The semi-finished product obtained in step (7) is aged for 18 hours in an environment with a temperature of 25°C and a relative humidity of 50%. Then it is cut into finished product specifications (A4 size single sheet or roll form), rolled up and packaged to obtain matte tattoo water transfer paper.

[0087] The matte tattoo water transfer paper prepared in Example 1 has a surface gloss of ≤15% (stable matte effect), good water solubility, and can begin to peel off after 3-5 seconds in 25℃ water, with complete peeling and no residue. The transferred pattern is clear, the matte texture is natural, it adheres closely to the skin, has good breathability, and does not wrinkle or fall off after 24 hours of wear. It is non-irritating to the skin and meets the requirements for tattooing. Figure 1 The images are of actual products. The left side shows the matte tattoo water transfer paper prepared in Example 1, and the right side shows ordinary water transfer paper.

[0088] Product performance test results:

[0089] Example 2 The main difference from Example 1 is: In the preparation of modified starch, the slip agent was replaced with oxidized polyethylene (molecular weight 3000, acid value 22mgKOH / g), and the amount added was 2.0% of the dry weight of starch.

[0090] The modified cellulose raw material was replaced with bleached hardwood pulp with a carboxymethylation degree of 0.65. The high-pressure homogenization pressure was 120 MPa, and the cycle was repeated 8 times.

[0091] Adhesive layer formulation: 25 parts modified starch, 22 parts modified cellulose, 18 parts natural rubber latex, 8 parts propylene glycol, 5 parts sorbitol, and 4 parts fatty alcohol polyoxyethylene ether (AEO-9).

[0092] Matte functional layer: The substrate is changed to PVC film (15μm thick), acrylic-polyurethane copolymer emulsion (45% solid content), fumed silica matting powder (average particle size 3μm) added in 12 parts, and polystyrene-maleic anhydride copolymer sodium salt dispersant.

[0093] Pattern carrier layer: 32 parts water-based acrylic resin, 12 parts gelatin emulsion, 2 parts fluorocarbon surfactant, 2 parts UV-328, 1.5 parts antioxidant 168, and 0.8 parts genipin acid.

[0094] Protective layer: PET film (15μm thick), with 10% triethyl citrate coating (relative to PET mass), dry lamination.

[0095] The matte tattoo water transfer paper prepared in this example has a surface gloss of ≤12% (for a softer matte effect), excellent water solubility, and can be delaminated in 2-4 seconds in 25℃ water, with fast delamination speed and no residue. After transfer, the pattern has rich colors and high clarity, the matte texture blends well with the skin, adheres tightly, has excellent breathability, and does not wrinkle or fall off after 48 hours of wear. It also passes the skin irritation test. Its overall performance is superior to existing high-gloss tattoo water transfer paper.

[0096] Product performance: Total thickness 142μm, 60° gloss 5.5 GU, water-wetting peel time 22 s, transfer integrity rate 95%, pattern durability 5.5 days.

[0097] Example 3 The main difference from Example 1 is: The natural rubber latex in the adhesive layer was replaced with a polyisoprene synthetic rubber latex with an equal solids content to examine the differences between natural and synthetic rubber.

[0098] The food-grade film-forming emulsion in the pattern carrier layer was replaced with chitosan emulsion (85% degree of deacetylation), and citric acid was added to adjust the pH to 5.5 to enhance the film-forming and antibacterial properties of chitosan.

[0099] The plasticizer for the protective layer was changed to triethyl acetylcitrate, with an addition amount of 25%.

[0100] Product performance: Total thickness 135μm, 60° gloss 7.2 GU, water wetting peel time 20 s, transfer integrity 96%, pattern durability 6.5 days (contributed by the water retention and skin adhesion of chitosan).

[0101] Comparative Example 1 The difference from Example 1 is as follows: The adhesive layer does not use modified starch and modified cellulose, but instead uses conventional polyvinyl alcohol (PVA) and sodium carboxymethyl cellulose (CMC, non-nanoized).

[0102] Results: Dry peel strength was 2.1 N / 25 mm (low, prone to delamination during storage), wet peel time was 35 s (long, inconvenient to use), and transfer integrity was 82%.

[0103] Comparative Example 2 The difference from Example 1 is as follows: The matte functional layer does not use silica matting powder, but only uses conventional acrylic emulsion coating.

[0104] Results: 60° gloss level 68 GU (high gloss, poor simulation), consumers subjectively felt it had a plastic feel.

[0105] Comparative Example 3 The difference from Example 1 is that the pattern carrier layer does not use food-grade film-forming emulsion and natural compounds, but uses industrial-grade styrene-acrylic emulsion and conventional industrial color paste.

[0106] Results: Two cases of mild erythema occurred in the skin irritation test; the pattern lasted for 3 days; there was no secondary color development effect of genipin, and the pattern lacked three-dimensionality.

[0107] Comparative Example 4 The difference from Example 1 is that the adhesive layer uses only modified starch and modified cellulose slurry, without adding natural rubber latex, and the rest is the same as Example 1; Results: The synergistic contribution of natural rubber to the film flexibility and peel smoothness enhances the non-obviousness of the ternary system.

[0108] Performance testing: 1. Test Items and Test Methods (1) Total thickness test: Refer to GB / T 451.3-2002 "Determination of thickness of paper and paperboard" and use a micrometer to test the total thickness of the sample. Ten different points are randomly selected for measurement and the average value is calculated.

[0109] (2) 60° Mirror Gloss Test: Refer to GB / T 9754-2007 "Determination of 20°, 60° and 85° Mirror Gloss of Paint Films without Metallic Pigments", test the 60° mirror gloss of the pattern surface after transfer, the unit is GU; the lower the value, the more significant the matte effect.

[0110] (3) Dry peel strength test: Refer to GB / T 2792-2014 "Test method for peel strength of adhesive tape", adopt 180° peel mode, peel speed 300mm / min, test the dry peel strength between the base paper layer and the functional layer, and reflect the interlayer bonding stability during product storage.

[0111] (4) Water wetting and peeling time test: Cut the sample into 50mm×50mm specimens and immerse them completely in pure water at 25℃. Record the time from the start of immersion until the pattern layer can be completely separated from the original paper layer without residue, reflecting the convenience of the transfer operation.

[0112] (5) Transfer integrity rate test: The pattern is transferred to the polyurethane simulated skin substrate using the standard transfer process, and the area of ​​complete pattern transfer is calculated by image analysis method; 100 parallel samples are tested in each group, and the average transfer integrity rate is taken.

[0113] (6) Pattern durability test: The simulated skin sample after transfer was placed in a cyclic aging environment: soaked in artificial sweat (pH=5.5) for 10 min → dry rubbed with 500g weight 10 times → UVB ultraviolet light irradiation for 2 h, which is one cycle; record the number of cycles when the pattern integrity drops to 80%, and convert it into the equivalent number of daily wear days.

[0114] (7) Color fastness to rubbing test: Dry rubbing test was conducted in accordance with GB / T 3920-2008 "Textiles Color Fastness Test - Color Fastness to Rubbing". After rubbing 10 times, the color fading grade was evaluated according to the gray sample card. The higher the grade, the better the rubbing performance.

[0115] (8) Skin irritation test: Referring to GB / T 16886.10-2017 "Biological evaluation of medical devices - Part 10: Irritation and skin sensitization test", a closed patch test was used to test the skin reaction of 30 healthy volunteers and observe the incidence of erythema and edema at 24h and 48h.

[0116] Table 2 shows the overall performance test results of each embodiment and comparative example:

[0117] Results Analysis: Matte Effect: Examples 1-3 and Comparative Examples 1 and 3 all achieved a high matte level (<10 GU). Comparative Example 2, due to the lack of matting powder, had a gloss level as high as 68 GU, proving that silica matting powder is the key to achieving a matte effect.

[0118] Interlayer bonding and transfer performance: The dry peel strength of Examples 1-3 were all in the range of 2.9-3.5 N / 25 mm, the wet peel time was 17-22 s, and the transfer integrity rate was 95-98%, showing excellent performance. Comparative Example 1, due to the use of a conventional PVA / CMC system, had lower peel strength, longer wetting time, and a transfer integrity rate of only 82%.

[0119] Pattern durability: Examples 1 and 2 lasted 6.0 days and 5.5 days, respectively. Comparative Example 3, due to the use of industrial-grade styrene-acrylic emulsion and the absence of natural film-forming substances, had a durability of only 3.0 days.

[0120] Color fastness to rubbing: Examples 1 and 3 reached level 4-5, Example 2 was level 4; Comparative Examples 1 and 3 were level 3-4 and level 3, respectively.

[0121] Skin irritation: Examples 1-3 are all grade 0 (non-irritating), and the use of food-grade / cosmetic-grade raw materials ensures the highest level of biocompatibility.

[0122] The above description is merely an exemplary embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A matte water transfer paper for tattoos, characterized in that, It is composed of a base paper layer, an adhesive layer, a matte functional layer, a pattern carrier layer, and a protective layer, which are sequentially laminated together. The adhesive layer is prepared from modified starch, modified cellulose slurry, natural rubber latex, polyol functional additives, and hydrophilic wetting agents; The matte functional layer is made of PET film or PVC film substrate, acrylic polymer resin, silica matting powder, anionic polymer dispersant and waterborne polyurethane stabilizer. The pattern carrier layer is made of water-based acrylic resin, food-grade film-forming emulsion, color paste wetting agent, weather-resistant color retention agent and natural compounds; The protective layer includes PET film or PVC film and citrate ester plasticizer.

2. The matte tattoo-specific water transfer paper according to claim 1, characterized in that, The mass fractions of each component in the adhesive layer are as follows: 20-40 parts modified starch, 10-25 parts modified cellulose, 15-30 parts natural rubber latex, 5-15 parts polyol functional additives, and 2-8 parts hydrophilic wetting additives.

3. The matte tattoo-specific water transfer paper according to claim 1, characterized in that, The method for preparing the modified starch includes: The original starch is prepared into a starch milk with a mass fraction of 5%~15%, heated to 60~95℃ for gelatinization, and after gelatinization, 0.5%-3% of the dry starch mass of the lubricant organic fluorine modified polysiloxane or oxidized polyethylene is added. After stirring evenly, it is dried, pulverized and sieved to obtain modified starch. The fluorine-modified polysiloxane has a fluorine content of 5% to 20% and a molecular weight of 3000 to 15000; the oxidized polyethylene has a molecular weight of 1000 to 5000 and an acid value of 15 to 30 mg KOH / g.

4. The matte tattoo-specific water transfer paper according to claim 1, characterized in that, The method for preparing the modified cellulose slurry includes: Cellulose raw materials are pretreated by carboxymethylation in a mixed solution of sodium hydroxide and monochloroacetic acid with a degree of substitution of 0.3 to 0.

8. The resulting sodium carboxymethyl cellulose is placed in deionized water to prepare a suspension with a mass fraction of 1% to 5%. After full swelling, it is circulated 5 to 20 times under a pressure of 50 to 150 MPa by a high-pressure homogenizer to dissociate and obtain nanocellulose with a diameter of 10 to 20 nm and a length of 200 to 1000 nm. The cellulose raw material is selected from at least one of bleached softwood pulp, bleached hardwood pulp, cotton pulp, or bamboo pulp; the homogenizing valve gap of the high-pressure homogenizer is 50~200μm, and the temperature is 20~60℃.

5. The matte tattoo-specific water transfer paper according to claim 1, characterized in that, The polyol functional additives are selected from at least one of propylene glycol, glycerol, sorbitol or polyethylene glycol; The hydrophilic wetting agent is selected from at least one of alkyl glycosides, fatty alcohol polyoxyethylene ethers, or succinate sulfonates. In the matte functional layer, the acrylic polymer resin is an aqueous acrylic emulsion or an acrylic-polyurethane copolymer emulsion with a solid content of 30%-50%. The silica matting agent is fumed silica or precipitated silica with an average particle size of 2-10 μm, and the amount added is 5%-20% of the solid content of the acrylic polymer resin. The anionic polymeric dispersant is sodium polyacrylate or sodium polystyrene-maleic anhydride copolymer; the waterborne polyurethane stabilizer is ionic waterborne polyurethane or self-emulsifying waterborne polyurethane.

6. The matte tattoo-specific water transfer paper according to claim 1, characterized in that, The citrate plasticizer is selected from at least one of acetylated tributyl citrate, triethyl citrate, acetylated triethyl citrate, or trioctyl citrate, and the amount added is 20% to 40% of the mass of the PVC substrate or 5% to 15% of the mass of the PET substrate.

7. The matte tattoo-specific water transfer paper according to claim 1, characterized in that, The mass fractions of each component in the pattern carrier layer are: 20-35 parts of waterborne acrylic resin, 10-20 parts of food-grade film-forming emulsion, 1-5 parts of color paste wetting agent, 30-50 parts of deionized water, 2-6 parts of weather-resistant color-preserving agent, and 0.5-3 parts of natural compound. The natural compound is genipin or genipin acid; The food-grade film-forming emulsion is selected from at least one of gum arabic, gelatin, or chitosan emulsion; the color paste wetting aid is selected from polyether-modified polysiloxane or fluorocarbon surfactant. The weather-resistant and color-preserving additive is a compound of ultraviolet absorber and antioxidant. The ultraviolet absorber is selected from at least one of UV-9, titanium dioxide or zinc oxide, and the antioxidant is selected from at least one of tocopheryl acetate or food-grade BHT.

8. The matte tattoo-specific water transfer paper according to claim 1, characterized in that, The thicknesses of each layer are as follows: base paper layer 80~150μm, adhesive layer 5~20μm, matte functional layer 10~30μm, pattern carrier layer 15~40μm, and protective layer 12~50μm.

9. A preparation process for matte tattoo-specific water transfer paper as described in any one of claims 1 to 8, characterized in that, Includes the following steps: (1) Pretreatment of the base paper layer: The base paper layer is subjected to corona treatment or coated with a base adhesive to enhance surface adhesion; (2) Adhesive layer coating: Modified starch, modified cellulose, natural rubber latex, polyol functional additives and hydrophilic wetting additives are mixed evenly and coated on the surface of the pretreated base paper layer, and then dried to form an adhesive layer; (3) Preparation of matte functional layer: Using PET film or PVC film as substrate, a matte functional coating is applied to one side of the substrate. The coating includes acrylic polymer resin, silica matting powder, anionic polymer dispersant, waterborne polyurethane stabilizer and deionized water, and is dried to form a matte functional layer. (4) Composite: The matte functional layer obtained in step (3) is hot-pressed with the smooth surface of the film substrate facing the adhesive layer and the matte coating surface obtained in step (2) facing upwards to obtain a composite semi-finished product; (5) Pattern carrier layer coating: The pattern carrier layer coating is applied to the matte coating surface of the composite semi-finished product obtained in step (4). The coating includes water-based acrylic resin, food-grade film-forming emulsion, color paste wetting agent, deionized water, weather-resistant color retention agent and natural compound, and is dried to form a pattern carrier layer. (6) Protective layer lamination: Using PET film or PVC film as the protective layer substrate, apply citrate ester plasticizer to its surface, with the side coated with plasticizer facing the direction of the pattern carrier layer, and lightly press and laminate it with the semi-finished product obtained in step (5). (7) Curing and slitting: The semi-finished product obtained in step (6) is cured in an environment with a temperature of 20~30℃ and a relative humidity of 45%~60% for 12~24 hours, and then slitting and rolling to obtain matte tattoo water transfer paper.

10. The preparation process of the matte tattoo-specific water transfer paper according to claim 9, characterized in that, In step (4), the hot-pressing composite temperature is 80~120℃ and the pressure is 0.3~0.8MPa; in step (6), the hot-pressing composite temperature is 100~150℃ and the pressure is 0.5~1.0MPa. In step (5), the gradient temperature drying is first pre-drying at 40~50℃ for 5~10 min, then main drying at 60~70℃ for 10~20 min, and finally final drying at 80~90℃ for 5~10 min.